Demographic and clinical differences between early- and late-onset bipolar disorders in a multicenter study in China. (30th December 2016) - Zhang, Ling; Yang, Hai-Chen; Xu, Xiu-Feng; Fang, Yi-Ru; Yu, Xin; Tan, Qing-Rong; Li, Hui-Chun; Ungvari, Gabor S.; Ng, Chee H.; Wang, Gang; Xiang, Yu-Tao
Abstract: Little is known about the demographic and clinical differences between early-onset (EOB) and late-onset bipolar disorders (LOB) in Chinese patients. This multi-center study examined the demographic and clinical characteristics of EOB (≤21 years) and LOB (>21 years) in China. A consecutively recruited sample of 555 patients with bipolar disorder (BD) from 7 psychiatric hospitals and general hospital psychiatric units across China was examined. Patients' demographic and clinical characteristics were collected using a standardized protocol and data collection procedure. There were 181 (34.8%) patients with EOB and 339 (65.2%) with LOB. Univariate analyses revealed that compared to the LOB group, the EOB group were more likely to be older, unemployed, have a longer illness duration, have BD-I and misdiagnosed as schizophrenia but were less likely to be misdiagnosed as major depressive disorder and receiving antidepressants. Multivariate analyses revealed that unemployment and longer duration of illness were independently associated with EOB. The clinical differences between early-onset and late-onset BD patients in China were largely consistent with those found in Western countries. Early-onset BD appear to be associated with poorer outcomes. Prospective studies examining the long-term outcomes in relation to age-at-onset are needed. Highlights: One third of Chinese patients had early onset bipolar disorder (≤21 years). Late onset patients were more likely to be misdiagnosed as major depressive disorder and receive antidepressants. Early onset was associated with more severe functional impairment. The demographic and clinical patterns in early-onset and late-onset bipolar patients in China were largely consistent with findings reported from Western settings.